A 30-year-old dermoid cyst - Zon, Erinna Mohamad; W Adnan, W Fadhlina; Planisamy, Kaamini; Mahmood, Nik Mohamad Zaki Nik (Bangladesh Journal of Medical Science, 2022)
Mature cystic teratoma (MCT) is the most common tumour of the ovary and includes at least two well-differentiated germ cell layers. The incidence is higher in reproductive age group and rarely among postmenopausal age women. It is benign condition however associated with multiple complication such as torsion, ruptured and chemical peritonitis. As it is rare among postmenopausal age group, it can be presented as chronic ovarian mass with expected complication and possibility of malignant transformation. Thorough assessment with adjunct of radiological imaging may assist in diagnosis and further management. Radiological imaging modalities were sensitive and sensitive in diagnosis of MCT however there were low specificity in detection of complication. Management of MCT in postmenopausal women mandate thorough evaluation considering the risk of malignant transformation and associated complications. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 918-921